Effect of the Stock Market on Economic Growth in Nepal - Bhandari, Khimananda (NPRC Journal of Multidisciplinary Research, 2025)
Background: This study examines the influence of stock market performance on Nepal’s economic growth from 1994 to 2024. Stock market variables, such as paid-up capital, the number of listed companies, market capitalisation, and turnover, are critical to understanding their role in the country's long-term economic performance. Previous literature suggests a potential relationship between financial market development and economic growth; nevertheless, the level of this relationship in the context of Nepal remains underexplored.Method: The analysis employs the Autoregressive Distributed Lag (ARDL) approach to measure the short- and long-term relationships between key stock market variables and Gross Domestic Product. This method is suitable given the mixed-order of integration in the data, covering the period from 1994 to 2024. Additionally, Granger causality tests are conducted to examine potential causal relationships between stock market performance and economic growth.Results: The study finds a significant long-term relationship between stock market performance, specifically paid-up capital and the number of listed companies, and Nepal's GDP. This highlights the importance of capital accumulation and market development in fostering sustained economic growth. Equally, market capitalisation, turnover, and government expenditure on education show limited or no significant effect on long-term economic growth. In the short run, real market capitalisation is found to negatively impact GDP. At the same time, turnover has no significant effect, suggesting that short-term market fluctuations do not directly contribute to economic growth. Diagnostic tests confirm the robustness and stability of the econometric model.Conclusion: The study stresses the importance of strengthening capital formation, promoting market listings, and encouraging investor participation to support economic growth in Nepal. Policy interventions should focus on improving market efficiency, investor protection, and integrating financial and human capital growth. The findings suggest that these measures can help align Nepal's stock market with its broader economic goals, promoting sustainable and inclusive growth.Novelty: This research offers new insights into the specific stock market variables that most significantly affect economic growth in Nepal, emphasising paid-up capital and the number of listed companies. By employing a robust econometric methodology and examining short-term and long-term relationships, this study contributes to the literature on financial market development. It suggests actionable policy recommendations for Nepal's economic policymakers.